Three Mothers, Three Daughters - Nancy L. Stockdale (International Institute of Islamic Thought, 2003)
In Three Mothers; Three Daughters: Palestinian Women's Stories, Rafiqa Othman and Michael Gorkin present six remarkable life narratives from Palestinian women living in the Occupied Territories and Israel. By selecting three mother/daughter pairs from very different social and political circumstances, they represent, in dramatic microcosm, many elements of the twentieth-century Palestinian experience. Moreover, these stories have a stunning universal appeal, transcending their specific national context by revealing complicated issues of gender and generational relations familiar throughout the world. In this way, Gorkin and Othman have crafted an oral history that is both specific to - and transcendent of - Palestine. From the outset of their collaboration, Gorkin and Othman wrestled with their complex personal positions and relationship, and used their preface and epilogue to frame their study in these terms. Gorkin is an American Jew living in Israel; Othman is a Palestinian Muslim from Abu Ghosh, the only Arab village on the Israeli side of the Green Line in the Jerusalem area to survive the 1948-49 war. Their collaboration was not only controversial because one is a Jew and the other an Arab, but also because being an unmarried woman, Othman confronted the issue of 'ayb (shame) falling upon her family if society misjudged her association with her male collalr orator. Moreover, several of the project's six informants would not speak with Gorkin because he is a man. Thus, Othman juggled a difficult problem that often faces scholars conducting anthropological research within their societies: a complicated status as both an insider and an outsider. It is to her credit that she deals directly with this issue. Othman points out her position as a confidante at times, and does not hesitate to draw on a common sense of "sisterhood" to relate to women's struggles. However, as an Arab living inside Israel, her ability to understand the experiences of Palestinians living under the occupation is difficult and painful. She reminds the reader that Palestinian experiences are as diverse as any others, and that at times she is as much a political outsider as Gorkin. The three mother/daughter pairs come from a relatively small territorial radius. However, the historical events and the borders emerging from ...